Broadband Strategies Handbook - Kelly, Tim (Washington, DC: World Bank, 2012)
The handbook consists of seven chapters and two appendixes that look at how broadband is defined, why it is important, and how its development can be encouraged. Throughout the handbook, broadband is viewed as an ecosystem consisting of supply and demand components, both of which are equally important if the expansion of broadband networks and services is to be successful. In addressing the challenges and opportunities to which broadband gives rise, the handbook discusses the policies and strategies that government officials and others should consider when developing broadband plans, including what legal and regulatory issues to address, what broadband technologies to choose, how to facilitate universal broadband access, and how to generate demand for broadband services and applications. Chapter one, 'building broadband,' introduces the concepts of broadband by defining the term 'broadband' more conventionally (that is, speed or functionality) as well as explaining how this handbook seeks to define the term as broadband comes to be seen as an enabling platform. Chapter two, 'policy approaches to promoting broadband development,' identifies the issues that governments and the private sector will face when developing policies and programs to support broadband development. Chapter three, 'law and regulation in a broadband world,' discusses the key policies and regulatory trends that policy makers and regulators are considering to foster broadband. Chapter four, 'extending universal broadband access and use,' discusses what roles governments should play in promoting universal broadband access when market mechanisms do not meet goals for broadband access and use on their own. Chapter five, 'technologies to support deployment of broadband infrastructure,' focuses on the supply side of the broadband ecosystem. It describes the various wireline and wireless technologies now being used to build out broadband infrastructure, including examples of broadband deployments throughout the world. Chapter six, 'driving demand for broadband networks and services,' recognizes that, although supply-side issues are important, simply building networks do not guarantee that they will be used or used most effectively. Chapter seven, 'global footprints: stories from and for the developing world,' addresses the main challenges that developing countries face in deploying broadband networks, including underdeveloped infrastructure, low income, significant differences between rural and urban areas, constrained inter- and intra-modal competition, and weaknesses in regulatory and legal frameworks.